BENTUK SOLIDARITAS SOSIAL PEDAGANG KAKI LIMA DALAM MEMPERTAHANKAN EKSISTENSI EKONOMI PEDAGANG (Jurnal Sosial Humaniora dan Pendidikan, 2023)
Society is a group of people who have lived side by side and worked together with the aim of being able to organize their lives and they constitute a social unit. Interconnected and living side by side so that the creation of social forces with their unique characters is an interesting social fact. Differences in social character regarding certain functions make individuals increasingly interdependent and become the basis for new forms of social solidarity. Humans are social creatures who cannot live alone but also need other humans. When living a human life with other humans, they have a function that contributes to fulfilling life's needs and realizing relationships between humans. Therefore, relations between people in a community group must be closer to create good relationships. Interaction activities between humans are very important. A key to social life is social interaction, if there is no social interaction there will be no life.